Ray Tracing RF Field Prediction: An Unforgiving Validation - E. M. Vitucci; V. Degli-Esposti; F. Fuschini; J. S. Lu; M. Barbiroli; J. N. Wu; M. Zoli; J. J. Zhu; H. L. Bertoni (International Journal of Antennas and Propagation)
The prediction of RF coverage in urban environments is now commonly considered a solved problem with tens of models proposed in the literature showing good performance against measurements. Among these, ray tracing is regarded as one of the most accurate ones available. In the present work, however, we show that a great deal of work is still needed to make ray tracing really unleash its potential in practical use. A very extensive validation of a state-of-the-art 3D ray tracing model is carried out through comparison with measurements in one of the most challenging environments: the city of San Francisco. Although the comparison is based on RF cellular coverage at 850 and 1900 MHz, a widely studied territory, very relevant sources of error and inaccuracy are identified in several cases along with possible solutions.